Thermus Bacteria and the Viruses That Infect Them - Ilmur Jónsdóttir 1996- (2020)
Thermus phages, much like Thermus bacteria, are of great interest in research due to their thermostability, in particular in regard to their enzymes and gene expression regulation. In this study, nine Icelandic thermophilic viruses that infect Thermus bacteria were investigated, as well as their relationship with selected strains isolated from Iceland and abroad. This was done by analysing the host-ranges of the phages, the genomes of the Thermus strains and phages, and the CRISPR/Cas systems. Viral lysates were prepared and quantified through the plaque assay method. The host ranges of the bacteriophages were analysed through cross-infection trials involving 27 Thermus strains from 11 different species. The results showed diversity in host ranges, as both unique and similar patterns were seen within and between Thermus species. Whole genome sequences of both bacteriophages and hosts were obtained using the Nanopore and Illumina sequencing methods. The sequence information was used to analyse the CRISPR/Cas systems of the Thermus strains. Five systems, Type IB, Type IC, Type IE, Type IIIA, and Type IIIB, were found in the Thermus genomes. Also, 1269 Thermus CRISPR spacers were identified. Immunity and infection seen through the cross-infection trials were cross-referenced to the CRISPR spacers and 30 protospacers were found in seven of the Thermus phages. The morphology of the viruses was analysed using transmission electron microscopy, which aided in their characterization and classification. The phages were classified into the families Myoviridae, Siphoviridae, Inoviridae, and Tectiviridae. This study was a part of the Virus-X (H2020) project and ultimately facilitated its aim, which was to expand the knowledge of the world‘s virosphere and develop novel viral enzymes for use in genetic engineering. Thermus veirur, líkt og Thermus bakteríur, eru mjög áhugaverðar vegna hitastöðugleika þeirra, einkum hvað varðar ensím þeirra og stjórnun gentjáningar. Markmið verkefnisins var að rannsaka níu íslenskar veirur ...